Chest wall resection and reconstruction for tumors: analysis of oncological and functional outcome - Scarnecchia, Elisa (J Thorac Dis, 2018)
BACKGROUND: Tumors of the chest wall have a large spectrum of well-assessed indications for resection. However, whether a reconstruction is required or not is not always clear. Complications after chest wall resection and reconstruction (CWRR) are described in literature and potentially severe. There is no evidence of how non-reconstructive management may influence the post-operative complication rate. METHODS: A total of 71 patients underwent thoracic demolition for tumors between April 2000 and October 2016. The patients were divided into two groups based on pathological findings: group 1: primary chest wall tumors; group 2: non-small cell lung cancer (NSCLC) invading the thoracic wall. They were then retrospectively analyzed by means of following criteria: TNM staging, histology, infiltration depth, 5-year survival, overall survival (OS), disease-free survival (DFS), relapse rate, R-0 resection, number of resected ribs, site of surgical resection and post-operative respiratory complications, flail chest, chronic pain, deformity of the chest wall and cosmetic results. RESULTS: Five-year survival, OS, DFS and risk of relapse showed a significant correlation with the presence of free surgical margins in both groups. In group 2, another parameter which correlated to survival, risk of relapse and DFS was lymph-nodal status. Moreover, the risk of post-operative respiratory complications was directly correlated with non-reconstruction after demolition of the chest wall in certain topographical sites. CONCLUSIONS: free surgical margins are the main oncological prognostic factor in these patients. In patients who underwent resection of two or more ribs in a critical area, reconstruction of the bony thorax can significantly reduce the post-operative respiratory complication rate.